Modeling vehicle agents for a VISSIM model of University of the Philippines - Diliman - Marasigan, Emmanuel D.; Palmiano, Hilario Sean O. (Quezon City College of Engineering, University of the Philippines Diliman, 2016)
Microscopic traffic simulation is a common approach in analyzing complex traffic system and transportation management. It is due to its flexibility as compared to traditional methods. It is also cheaper, safer and faster. However, to give meaningful and reliable results, simulation models must be calibrated properly. Many literatures are available suggesting methodologies in calibrating and validating simulation models. The key procedures proposed in the studies involve accurately representing the local condition in the network constructed, performing sensitivity analysis in reducing the calibration parameters, running an optimization algorithm to estimate behavioral parameters and validating the calibrated model. Another important element is the determination of a measure of performance to be used as the objective function in the optimization. Travel time was used as the measure of performance for the study and the test track included a signalized intersection inside the university. The study was able to address possible factors that greatly affected the modeling of vehicles in UP Diliman, specifically accelerations, conflict areas and overtaking in the opposing direction.
Thesis (B.S. Civil Engineering)--University of the Philippines Diliman
Keywords: Traffic flow -- Simulation methods; Transportation -- Mathematical models; Traffic flow -- University of the Philippines